Analisis Implementasi Pencatatan Perkawinan menurut Peraturan Menteri Agama dan Hukum Islam - M Alvin Nuzi Khairi Mazin; Siska Lis Sulistiani (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. In carrying out its duties, KUA it has been regulated in the Regulation of the Minister of Religion (PMA) Number 20 of 2019 concerning Marriage Registration. One form of Islamic family law reform is the inclusion of marriage records as one of the marriage provisions that must be met. This study aims to analyze the implementation of marriage registration at KUA Bojongsoang according to Article 40 PMA Number 20 of 2019 and Islamic Law. This research is juridical normative. Data obtained through interviews and literature study. The data analysis technique used is Content Analysis and Descriptive Analysis. The results of the study show that the implementation of Marriage Registration at KUA Bojongsoang is not in accordance with Article 40 PMA Number 20 of 2019, this is evidenced by still publishing duplicate marriage books in sheet form. However, according to Islamic law, marriage registration carried out by KUA Bojongsoang is in accordance with the definition of maslahah which means a good thing, which is useful, so that marriage registration has provided maslahah for the community in Bojongsoang District in order to obtain legal certainty by proving the marriage book. for various matters that require it administratively. Abstrak. Dalam melaksanakan tugasnya KUA telah diatur dalam Peraturan Menteri Agama (PMA) Nomor 20 Tahun 2019 Tentang Pencatatan Perkawinan. Salah satu bentuk pembaruan hukum keluarga Islam adalah dimuatnya pencatatan perkawinan sebagai salah satu ketentuan perkawinan yang harus dipenuhi. Penilitian ini bertujuan untuk menganalisis implementasi pencatatan perkawinan di KUA Bojongsoang menurut Pasal 40 PMA Nomor 20 Tahun 2019 dan Hukum Islam. Penelitian ini bersifat yuridis normatif. Data diperoleh melalui wawancara dan studi pustaka. Teknik analisis data yang digunakan adalah Analisis Isi (Content Analisys) dan Analisis Deskriptif. Hasil penelitian menunjukan bahwa implementasi Pencatatan Perkawinan di KUA Bojongsoang belum sesuai dengan Pasal 40 PMA Nomor 20 Tahun 2019, hal ini dibuktikan dengan masih menerbitkannya duplikat buku nikah dalam bentuk lembaran. Namun, menurut hukum islam pencatatan perkawinan yang dilaksanakan KUA Bojongsoang sudah sesuai dengan melihat akan definisi dari maslahah yang mempunyai makna suatu hal yang baik, yang berguna, sehingga pencatatan perkawinan itu sudah memberikan maslahah untuk masyarakat di Kecamatan Bojongsoang guna mendapatkan kepastian hukum dengan dibuktikannya buku nikah untuk berbagai hal yang mensyaratkannya secara administratif.